Izbrani vidiki pravice do izjave v azilnih postopkih - Šelih, Urh (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2024)
The paper discusses the importance of the right to be heard in asylum procedures, focusing on its role in both assessing the risk of refoulement and granting international protection. The main thesis is that the statements of asylum seekers, obtained through personal interviews, form a key basis for subsequent proceedings and decision-making by the competent authorities. These statements are particularly important in cases where applicants have no other evidence, which is a common occurrence. The articleexamines the legal aspects and requirements of the right to be heard as they arise under European Union law, the European Convention on Human Rights, and national law. Its main purpose is to present several key aspects of this right, particularly in the context of the procedural requirements laid down by European and national legal sources. These aspects include the procedural rights of applicants, such as the right to comment on the report of the personal interview and the right to comment on the competent authorities’ findings regarding the credibility of statements and evidence. The article concentrates on the most significant and problematic aspects of the right to be heard that demand special attention in the processing of asylum applications. The author argues that the right to be heard is not confined to a personal interview but also requires the opportunity to provide additional information, correct errors, and comment on the findings of the competent authorities. The article additionally analyses relevant case law supporting the argument about the importance of the right to be heard in asylum proceedings.
Keywords: asylum; azil; duty to cooperate; international protection; mednarodna zaščita; pravica do izjave; Procedures Directive; procesna direktiva; right to be heard; sodelovalna dolžnost